Politics, citizenship and disobedience in the city of crisis: a critical analysis of contemporary housing struggles in Madrid - Janoschka, Michael (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
The city region of Madrid can be considered as an exponent of the striking contradictions associated with the contemporary market-oriented production of housing. Given the increasing economic constraints of many middle- and working-class households because of the crisis, property values have been declining for practically seven years now, and tens of thousands of households have been evicted from their homes because they were unable to pay back their mortgages. Simultaneously, since the outbreak of the indignados movement in May 2011, a contestation of the structural forces ruling the real estate sector has been taking place, and questions about the right of housing became a prominent part of the public debate in an increasingly politicised society. Alongside the background of literature about the post-political city and subversive citizenship, this article pursues three key aims: It analyses the consequences of the persistent crisis with a special focus on the residential housing market in Madrid. Secondly, an analysis of the new social and political dynamics that have been emerging during the crisis is developed. Finally, it pinpoints to the way how the emergence of new actors within contemporary housing struggles has been shifting the social and political discourses in this political arena. Such an approach brings together discussions from the field of Political Science with the new geographies of contested crisis urbanism that relate to debates about the social construction of the city, citizenship and disobedience.